Immunohistochemical diagnosis of onychomycosis by monoclonal antibodies detection of dermatophyte T. rubrum. (28th October 2021) - Audon, P; Sigurdarson, H; Guzman, Y; Hua, C; Bach, M; Bach, D; Villaluz, S
Abstract: Introduction/Objective: Onychomycosis is one of the most common nail infection disorders, caused predominantly by T. rubrum. Currently, PAS stain is the gold standard for histological onychomycosis detection. However, it does not differentiate between the types of fungi. In addition, PAS stains will only provide a positive or negative result. This leaves physicians to prescribe medications that may be ineffective in treating the root cause of the infection. By discerning the causative specie, physicians can provide a more targeted and effective anti-fungal therapy. A novel monoclonal antibody can be utilized to improve histological findings of T. rubrum. Our study takes a step forward to bring the monoclonal antibody into histological application. We have developed a new monoclonal antibody stain which binds to T. rubrum in vitro. For our project, we will perform in vivo staining on clinical nail samples using the novel monoclonal antibody. Developing a new applicable technique will benefit patients with onychomycosis as well as promote research in targeted identification of other infectious pathologies. Methods/Case Report: Data from Bach Dx's collaboration demonstrate isolation and validation of mice monoclonal antibody candidates for T. rubrum. Isotype IgG1/kappa 17B6 had the highest binding pair signal to the analyte. Direct ELISA of 17B6.1E3 shows immunoreactivity to T. rubrum. HRP and AP conjugates to 17B6 mice monoclonal antibody are produced (Rockland Immunochemicals Inc. Gilbertsville, PA). Histology slides analyzed for routine onychomycosis analysis at Bach Diagnostics are subject to secondary analysis. 220 retrospective, unstained nail slides from 55 patients will be stained using the 17B6 stains. 40 patients were known to have tested for onychomycosis caused by T. rubrum, 5 by Candida albicans, 5 by T. interdigitale, and 5 tested negative. All samples were confirmed by histology and molecular tests. H&E, PAS, and naked antibody stains will serve as controls. HRP and AP conjugated 17B6 monoclonal antibody stains will be optimized to Quantum Hdx (StatLab Lodi, CA) on July 12th, 2021 when the stains are scheduled to arrive. Images will be captured by light microscopy, and analyzed quantitatively and qualitatively. Results (if a Case Study enter NA): We hope to show preferential staining of antibody stains to positive T. rubrum cases by end of July 2021. Conclusion: Conclusion pending based on results.